IMPROVING STUDENTS PARTICIPATION IN QUESTIONS AND ANSWERS THROUGH PROBING AND PROMPTING LEARNING TECHNIQUE IN SOCIAL SCIENCE LEARNINGS (Act Research of VIII-C Class of Junior High School Kartika XIX-2 Bandung) - Rahayu, Yunia Firdausi (International Journal Pedagogy of Social Studies, 2016)
Background of this research is about issue that exist in VIII-C class of Junior High School Kartika XIX-2 Bandung there are less of participations students in questions and answer in social science learnings. This is because social science learnings has less involve of students. Based on the issue, it needs to be done some repraration which can make students get involved directly in social science learnings. Researcher choose clas act research (CAR) with model design investigation Kemmis Mc. Taggart (1998) that consist of planning, implementation, observation and reflections that consent in three cycle. Researcher try to improve students participation with probing and prompting learning technique in social science learnings. The successful of this research of this research can be seen from the improvement of learning participations which are showed through the development from some indicators; one of them is students emotional and mental involvement. Students willingness give contribution to reach the purpose and enthuasiasm in learning which can give advantages for students. In the research, the biggest obstacle was the difficults in escalating students ,otivations to read various information regarding materials. The result of the research proves that the application of the learning technique probing and prompting learning is definitely effective in improving students participation in questions and answer of social science learning.Â